2018
DOI: 10.1016/j.energy.2018.04.048
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of temperature glide matching of heat pumps with zeotropic working fluid mixtures for different temperature glides

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…In refrigeration systems and heat pumps the main benefits of working fluid mixtures lie in the expansion of the availability of working fluids for system optimization, the compensation of undesirable properties of one of the components (e.g. flammability, global warming potential), as well as on the performance increase due to the improved temperature matching between the fluids exchanging heat [3]. In organic Rankine cycle power systems, the temperature glide represents the main advantage of their use, as it contributes to reduce irreversibilities during the phase change, resulting in better thermodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…In refrigeration systems and heat pumps the main benefits of working fluid mixtures lie in the expansion of the availability of working fluids for system optimization, the compensation of undesirable properties of one of the components (e.g. flammability, global warming potential), as well as on the performance increase due to the improved temperature matching between the fluids exchanging heat [3]. In organic Rankine cycle power systems, the temperature glide represents the main advantage of their use, as it contributes to reduce irreversibilities during the phase change, resulting in better thermodynamic performance.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that employing an inner heat exchanger expands the performance of the plant by 5.5% and heating capacity by 5% when the mentioned mixture refrigerant was employed. Zühlsdorf et al 39 analyzed the temperature glide matching of heat pumps using zeotropic refrigerant by considering various temperature glides, and Fan et al 40 determined the functionality of the heat pumps with zeotropic mixtures specifically for district cold region. Mixture of R‐32/R‐290 was concluded to have the best performance among other mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…The development status of HTHPs configurations is still mostly limited to theoretical analysis, such as those performed by Cao et al, and Mateu-Royo et al [11,12], which considered an external heat exchanger in one and two stages, or those performed by Mota-Babiloni et al and Yang et al [13,14], which considered HTHP cascades. Moreover, an intensive theoretical study was performed on the energy performance benefits provided by the use of zeotropic mixtures [15,16].…”
Section: Introductionmentioning
confidence: 99%